EFEKTIVITAS MEDIA EDUKASI AUDIO VISUAL DAN BOOKLET TERHADAP PENGETAHUAN PREMENOPAUSE, EFIKASI DIRI DAN STRESS PADA WANITA PREMENOPAUSE - Novita Anggraini; Bela Purnama Dewi; Eliyah (Jurnal Kesehatan dan Pembangunan, 2023)
Premenopause is the emergence of early signs and symptoms of changes in the body's system when the menstrual cycle begins to become irregular. One way to prepare women to face premenopause is by changing their cognition through providing education using audio-visuals and booklets as media. The aim of the study was to determine the effectiveness of audio-visual media and booklets on premenopausal knowledge, self-efficacy and stress in premenopausal women outpatient polyclinics at Kayu Agung Hospital in 2022. The research method used the pre-experimental research design with a one-control design approach. The research results obtained data that there was an influence of audio-visual educational media and booklets on premenopausal women with a p value for knowledge of 0.000 and a p value of self-efficacy = 0.000 and a p value for stress = 0.000. Audio-visual and/or booklets about premenopause can be used as educational media in an effort to increase premenopausal women's knowledge about the physiological and psychological changes that occur during the premenopausal period, so that premenopausal women become confident and able to deal with the changes that occur. In the end premenopausal women will be able to prevent and overcome stress.